ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK MUAMALAT INDONESIA DAN BANK SYARIAH MANDIRI - Ema Dwi Suryani; Dyah Fitriani (Jurnal Fokus Manajemen Bisnis, 2013)
The purpose of this study was to assets the financial performance of Bank Muamalat Indonesia in 2010-2014, assets the financial performance of Bank Syariah Mandiri in 2010-2014, to know is there any difference in the performance of Bank Muamalat Indonesia and Bank Syariah Mandiri in 2010-2014. This data source which used are secondary data in the form of financial statements of the company obtained from the publication of Bank Indonesia. Data analysis was performed using analysis of financial ratios of capital adequacy ratio, asset quality ratios, profitability ratios and liquidity ratios. The method used to compare the performance of Bank Muamalat Indonesia with Bank Syariah Mandiri is using the test independent sample t test. Based on the calculation of independent sample t test showed that for each ratio is the ratio Provision of Minimum Capital Adequacy Ratio (CAR), the ratio of asset quality (KAP), the ratio of Net Operational Margin (NOM) and the ratio of Short Term Mismatch (STM) there was no difference in financial performance significantly between Bank Muamalat.